Physiological characteristics of blood pressure responses after combined exercise in elderly hypertensive patients: a systematic review and meta-analysis - Li, Zhiheng; LV, Moran; Li, Zhen; Gao, Wei; Li, Ming (Frontiers in Cardiovascular Medicine, 2024)
Objective: The aim of this investigation is to explore the efficacy of combined exercise in elderly patients with hypertension. Moreover, we aim to delve into the underlying mechanisms governing blood pressure regulation, with the objective of promoting the adoption of this exercise regimen among elderly hypertensive individuals.In our study, we conducted a thorough search across multiple databases, including PubMed, Web of Science, Cochrane Library, Embase, and Scopus. This extensive search resulted in the preliminary screening of 2347 articles. Among these, 9 studies were carefully selected for an indepth analysis. For our meta-analysis, we employed Review Manager 5.3 and Stata 15.0, enabling us to perform detailed subgroup analyses and assess the possibility of publication bias.In comparison to the control group (n=194), individuals enrolled in the combined exercise group (n=200) exhibited a notable decrease in both resting systolic blood pressure (SBP) [weighted mean difference (WMD) = -11.17 mm Hg, 95% confidence interval (CI) (-17.13, -5.22), Z=3.68, P<0.05] and diastolic blood pressure (DBP) [WMD = -5.93 mm Hg, 95% CI (-9.24, -2.61), Z=3.51, P<0.05]. Nonetheless, no statistically significant alteration was observed in pulse pressure (PP) [WMD = -9.05 mm Hg, 95% CI (-22.65, 4.55), Z=1.3, P=0.192]. Further subgroup analyses elucidated that combined exercise regimens, characterized by aerobic training intensities below 85% of HRmax, durations of up to 12 weeks, weekly frequencies of either ≥3 or <3 sessions, total session times under 60 minutes, and a sequence of aerobic exercise followed by resistance training (AE-RT), were particularly effective in enhancing SBP and DBP among elderly patients with hypertension.Additionally, regular engagement in combined exercise led to significant improvements in SBP and DBP across individuals aged 60-70, those older than 70 years, and regardless of whether participants were using antihypertensive medications or not.Combined exercise serves as an efficacious adjunctive therapy for reducing blood pressure among elderly individuals with hypertension, exerting beneficial influences on multiple physiological mechanisms pertinent to blood pressure regulation. Moreover, the integration of aerobic exercise with resistance training presents a more varied training program, thereby eliciting wider-ranging positive effects on both the physical and mental well-being of elderly patients afflicted with hypertension.